Islamic Spiritual Guidance in Reducing the Anxiety of Chemotherapy Patients with Spiritual Emotional Technique (SEFT) - Latifatul Khairul Umam; Aep Kusnawan; Isep Zaenal Arifin (al-Afkar, Journal For Islamic Studies, 2024)
Chemotherapy patients frequently have high anxiety levels because of a variety of factors, including their environment and the information they are given, their lack of knowledge about the chemotherapy procedure, the physical decline they go through, and their worries about the family they leave behind. Given the significance of a successful course of treatment, chemotherapy patients should receive Islamic spiritual counsel. In Al Ihsan Hospital, Islamic spiritual guidance specifically designed to lessen chemotherapy patients' anxiety can use the Spiritual Emotional Freedom Technique (SEFT) as part of the guidance. The research adopts a qualitative approach with descriptive methods. Data collection techniques include interviews, observations, and documentation. The informants in this study are the researcher as the spiritual guide, chemotherapy patients, and chemotherapy nurses. The results of this study indicate that the anxiety conditions of chemotherapy patients are influenced by personal and social factors, with variations ranging from mild to panic anxiety. The spiritual guidance provided using SEFT involves the delivery of Quranic verses and historical stories to strengthen faith and SEFT techniques to address anxiety.